2016
DOI: 10.2147/ijn.s107292
|View full text |Cite
|
Sign up to set email alerts
|

Charge effect of a liposomal delivery system encapsulating simvastatin to treat experimental ischemic stroke in rats

Abstract: Background and aims Although the beneficial effects of statins on stroke have been widely demonstrated both in experimental studies and in clinical trials, the aim of this study is to prepare and characterize a new liposomal delivery system that encapsulates simvastatin to improve its delivery into the brain. Materials and methods In order to select the optimal liposome lipid composition with the highest capacity to reach the brain, male Wistar rats were submitted to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…These nanoparticle properties can influence the distribution of nanoparticles within the body. 31 The particle size and zeta potential are the main factors affecting the nanoparticle cellular uptake, as observed for other nanoparticles such as polymeric and inorganic particles. 28 The small size of the particles makes nanotechnology very useful in medicine, but it may cause adverse effects in humans.…”
mentioning
confidence: 96%
“…These nanoparticle properties can influence the distribution of nanoparticles within the body. 31 The particle size and zeta potential are the main factors affecting the nanoparticle cellular uptake, as observed for other nanoparticles such as polymeric and inorganic particles. 28 The small size of the particles makes nanotechnology very useful in medicine, but it may cause adverse effects in humans.…”
mentioning
confidence: 96%
“…21,22,52 The distribution of the nanoparticles within the body is mainly influenced by these characteristics. 53 The release profile of TQ-NLC showed that the concentration of TQ released by NLC was not equivalent to the concentration of TQ alone even after 72 h. Hence, in contrast to pure TQ solution (which showed the burst release profile), the absence of concentration spike was anticipated when the cells were treated with TQ-NLC. 54 lymphatic systems.…”
Section: Discussionmentioning
confidence: 93%
“…It is crucial that liposomes can cross the BBB and it is also desirable that they remain in the bloodstream for a long period of time, so as to deliver a sufficient quantity of drug to the brain tissue ( Moghimi et al, 2001 ). The circulation time of liposomes can be enhanced through reduction of particle size or modification of their surface by polyethylene glycol (PEG) ( Fukuta et al, 2014 ; Bozzuto and Molinari, 2015 ; Wang et al, 2015 ; Campos-Martorell et al, 2016 ; Chen and Gao, 2017 ). It has been reported that PEGylated liposomes can accumulate into ischemic brain regions after a stroke event ( Fukuta et al, 2016 ), presumably because of the disruption of the BBB and the enhanced vesicle permeation and retention at the ischemic site.…”
Section: Liposomes As Drug Nanocarriersmentioning
confidence: 99%
“…The surface charge is another factor that can influence the accumulation of liposomes into the brain. Campos-Martorell et al (2016) showed that neutral and negatively charged PEGylated liposomes administered intravenously were captured to a lower extent by the liver and lungs in comparison to cationic vesicles. As consequence, the neutral and anionic liposomes showed prolonged circulation time in the blood and higher uptake in the ischemic region ( Campos-Martorell et al, 2016 ).…”
Section: Liposomes As Drug Nanocarriersmentioning
confidence: 99%
See 1 more Smart Citation